International joint venture of two giants in the CRT industry: strategy analysis using system dynamics. (1st January 2002) - Tang, Victor; Lee, Man-Hyung
The past decade has seen a dramatic rise in the number international joint ventures (IJV) and a great majority of them fail. Although the research literature continues to expand, there is an imbalance to the attention paid to the process and operational management side of IJVs. We begin this article with a survey of the literature and we segment the research stream into the life cycle phases of an IJV: the IJV input, process, and output schools of investigation. Then, we present an overview of the Cathode Ray Tube (CRT) industry and the competitive forces that influenced LG and Philips to form a strategic joint venture. Next, which is the core of this article, we use the disciplines of system dynamics to perform strategy analyses of the dynamics of the LG-Philips IJV. The fundamental intent of this paper is to demonstrate how system dynamics is an effective analytic instrument to derive strategic measures, as well as countermeasures to strengthen the IJV operations and to weaken competitors and blunt the impact of their actions. We show how we can model technology-intensive businesses, in the context of industries and markets, by means of systems with intricate and technology-idiosyncratic feedback characteristics, but whose complex system behaviour is substantially more easily discernable from their graphic representations. Fourth, we close this article with a discussion on the limitations of our analysis and potential areas for further research.